Sistem Informasi Pengelolaan Kios Berbasis Website Pada Poli Kios Yogyakarta - Linda Apriyanti; Abdurrahman Abdurrahman; Windah Utari (Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2023)
Poli Kiosk is a kiosk rental for the people of Yogyakarta, but the shop ordering process records customer data manually. This Poli Kiosk rental in the management of rental transactions still uses a manual system. From the existing problems, the author wants to apply information provision technology that can help manage Poli Kiosk rental transactions. In developing a Website-Based Kiosk Management Information System at Poli Kiosk Yogyakarta, the author uses the waterfall development method, with the UML system model and system development using the programming language (PHP5) and (HTML5) and the Laravel framework. Based on the results of the study, it was concluded that the information system created could help manage rental transactions and provide information on Kiosk rentals.